Habit in its relation to thought - Cummings, Charles William (My University, 1905)
Introduction: In the treatment of such abstract subjects as Habit and Thought we must define them in terms of what they do, in what results they produce rather than in what they are. For our purpose a Habit may be defined as an act which has been consciously preformed so many times that it is at last able to go on of itself while the brain is engaged in other thought. But the knowledge or sensation that the act is going on is present in the brain. Thought or thinking is the process through which the mind passes in getting possession of an idea or for our purpose the process through which the brain passes before a given act is performed. It can thus be seen that as habits are simply the results of thought processes which engaged the whole attention of the brain at first and which through repetition became more or less automatic, and it is evident that the more such processes are automatic the more time and freedom is given to the brain for acquiring new ideas.
Citation: Cummings, Charles William. Habit in its relation to thought. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Habit Speeds Action; Habit Frees Brain for Other Work; Habit Makes Complicated Tasks Possible; Theses; Manuscripts (documents)